Effect and mechanism of paclitaxel loaded on magnetic Fe3O4@mSiO2-NH2-FA nanocomposites to MCF-7 cells - Yun Ni; Peng Deng; Ruitong Yin; Ziye Zhu; Chen Ling; Mingyi Ma; Jie Wang; Shasha Li; Ruijiang Liu (Taylor & Francis Group, 2023)
AbstractMagnetic Fe3O4 nanoparticles were prepared via a simple hydrothermal method and utilized to load paclitaxel. The average particle size of Fe3O4 nanoparticles was found to be 20.2 ± 3.0 nm, and the calculated saturation magnetization reached 129.38 emu/g, verifying superparamagnetism of nanomaterials. The specific surface area and pore volume were 84.756 m2/g and 0.265 cm3/g, respectively. Subsequently, Fe3O4@mSiO2 nanoparticles were successfully fabricated using the Fe3O4 nanoparticles as precursors with an average size of 27.81 nm. The relevant saturation magnetization, zeta potential, and specific surface area of Fe3O4@mSiO2-NH2-FA were respectively 76.3 emu/g, −14.1 mV, and 324.410 m2/g. The pore volume and average adsorption pore size were 0.369 cm3/g and 4.548 nm, respectively. Compared to free paclitaxel, the solubility and stability of nanoparticles loaded with paclitaxel were improved. The drug loading efficiency and drug load of the nanoformulation were 44.26 and 11.38%, respectively. The Fe3O4@mSiO2-NH2-FA nanocomposites were easy to construct with excellent active targeting performance, pH sensitivity, and sustained-release effect. The nanoformulation also showed good biocompatibility, where the cell viability remained at 73.8% when the concentration reached 1200 μg/mL. The nanoformulation induced cell death through apoptosis, as confirmed by AO/EB staining and flow cytometry. Western blotting results suggested that the nanoformulation could induce iron death by inhibiting Glutathione Peroxidase 4 (GPX4) activity or decreasing Ferritin Heavy Chain 1 (FTH1) expression. Subsequently, the expression of HIF-1α was upregulated owing to the accumulation of reactive oxygen species (ROS), thus affecting the expression of apoptosis-related proteins regulated by p53, inducing cell apoptosis.